Network performance in Kumpulan IKRAM Sdn Bhd: a case study / Zam Zarina Abdul Jabar - Abdul Jabar, Zam Zarina (2004)
In general, network management is a service that employs a variety of tools, applications, and devices to assist network administrator or network managers in monitoring and maintaining networks. There are five conceptual areas of network management which are network performance management, configuration management, accounting management, fault management, and security management. This research will concentrate on network performance management. The goal of network performance management is to measure and make available various aspects of network performance so that Internetwork performance can be maintained at sufficient level. Examples of performance variables that might be provided include network throughput, network availability, response times, bandwidth, and utilization. There are two types of network performance tools that will be used in this research which is Ping program and CommView network .performance software. This case study also will find out whether network architecture can affect the network performance or not. The case study is being made in Kumpulan IKRAM Sdn Bhd.